Conservative management of cervical pregnancy with embryonic heart activity by ultrasound-guided local injection: an eight case series. (September 2014) - Júnior, Julio Elito; Musiello, Rubens Bermudes; Araujo Júnior, Edward; Souza, Eduardo; Fava, Jair Luiz; Guerzet, Eduardo Almeida; Camano, Luiz
Abstract Objective: To evaluate the efficacy of conservative management of cervical pregnancy with embryonic heart activity by ultrasound-guided local injection. Methods: Retrospective case series at University tertiary care Hospital. Eight patients diagnosed with cervical pregnancy with embryonic heart activity managed conservatively. The intervention was ultrasound-guided local injection of methotrexate (1 mg/kg) and potassium chloride (2 meq/mL). Measurements were occurrence of morbidity, necessity for further intervention, the initial titers of beta-hCG, interval of time in which the levels of beta-hCG became negative, period for regression of cervical pregnancy at ultrasound and future pregnancy. Results: All patients were treated successfully. The initial levels of beta-hCG ranged from 3013 to 71199 mUI/mL. One case evaluated with infection. There was no need for additional intervention in our series study. The interval of time for the levels of beta-hCG becomes negative range from 2 to 12 weeks. The period for the regression of the cervical pregnancy at ultrasound range from 3 to 14 weeks. In two cases intrauterine pregnancies occurred after the treatment. Conclusion: Conservative management of cervical pregnancy with embryonic heart activity by ultrasound-guided injection is an effective treatment avoiding the need of further intervention.